Asexual Reproduction Does Not Apparently Increase the Rate of Chromosomal Evolution: Karyotype Stability in Diploid and Triploid Clonal Hybrid Fish (Cobitis, Cypriniformes, Teleostei) - Majtánová, Zuzana; Choleva, Lukáš; Symonová, Radka; Ráb, Petr; Kotusz, Jan; Pekárik, Ladislav; Janko, Karel (PloS one, 2016)
Interspecific hybridization, polyploidization and transitions from sexuality to asexuality considerably affect organismal genomes. Especially the last mentioned process has been assumed to play a significant role in the initiation of chromosomal rearrangements, causing increased rates of karyotype evolution. We used cytogenetic analysis and molecular dating of cladogenetic events to compare the rate of changes of chromosome morphology and karyotype in asexually and sexually reproducing counterparts in European spined loach fish (Cobitis). We studied metaphases of three sexually reproducing species and their diploid and polyploid hybrid clones of different age of origin. The material includes artificial F1 hybrid strains, representatives of lineage originated in Holocene epoch, and also individuals of an oldest known age to date (roughly 0.37 MYA). Thereafter we applied GISH technique as a marker to differentiate parental chromosomal sets in hybrids. Although the sexual species accumulated remarkable chromosomal rearrangements after their speciation, we observed no differences in chromosome numbers and/or morphology among karyotypes of asexual hybrids. These hybrids possess chromosome sets originating from respective parental species with no cytogenetically detectable recombinations, suggesting their integrity even in a long term. The switch to asexual reproduction thus did not provoke any significant acceleration of the rate of chromosomal evolution in Cobitis. Asexual animals described in other case studies reproduce ameiotically, while Cobitis hybrids described here produce eggs likely through modified meiosis. Therefore, our findings indicate that the effect of asexuality on the rate of chromosomal change may be context-dependent rather than universal and related to particular type of asexual reproduction.
Keywords: Cypriniformes; Diploidy; triploidie; máloostní; Animals; karyotyp; Reproduction, Asexual; biologická evoluce; diploidie; ženské pohlaví; Female; Biological Evolution; Triploidy; nepohlavní rozmnožování; zvířata; Karyotype